2015
DOI: 10.17116/jnevro201511511155-62
|View full text |Cite
|
Sign up to set email alerts
|

Experience of the antidepressive therapy with valdoxan (agomelatine) in a psychogeriatric unit of the psychiatric hospital

Abstract: Valdoxan can be recommended for treatment of mild and moderate depression in inpatients of psychiatric hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…However, these results must not be overinterpreted as they are based only on the small numbers of patients included in studies of older depressed patients. 40,41 Agomelatine has not been approved for use in the United States. No long-term data on the use of agomelatine in LLD are available and such studies are needed to provide data concerning the tolerability of agomelatine in older patients, including the adverse effect of sedation and a possible increase in liver enzyme values.…”
Section: Key Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these results must not be overinterpreted as they are based only on the small numbers of patients included in studies of older depressed patients. 40,41 Agomelatine has not been approved for use in the United States. No long-term data on the use of agomelatine in LLD are available and such studies are needed to provide data concerning the tolerability of agomelatine in older patients, including the adverse effect of sedation and a possible increase in liver enzyme values.…”
Section: Key Resultsmentioning
confidence: 99%
“…The melatonergic agonist and 5HT2c-receptor antagonist agomelatine, which was approved for unipolar depression in Europe in 2009 but has not been approved in the United States, was investigated as an antidepressant in elderly people with recurrent MDD in 2 studies. [39][40][41] In a placebo-controlled trial involving 222 patients who were 65 years of age or older, Heun et al 40 found a 6.9% difference in remission rates between the agomelatine and placebo groups after an 8-week-treatment favoring agomelatine, although the difference was not statistically significant. However, agomelatine was found to be effective and well-tolerated in reducing depressive symptoms and to have a good adverse effect profile in the geriatric and comorbid study population.…”
Section: Other Antidepressants Agomelatinementioning
confidence: 99%
See 1 more Smart Citation
“…Some open evaluations in small populations have suggested a good therapeutic effect in elderly populations. In these studies, 6-12 weeks treatment with agomelatine 25-50mg/day was reported to lead to a significant reduction in depressive symptoms [65][66][67][68]. A double blind placebo controlled trial did not support the efficacy of agomelatine however, this trial lacked assay sensitivity due to a high placebo response rate [69].…”
Section: Agomelatinementioning
confidence: 99%
“…Case reports suggest a potential of agomelatine as treatment for social anxiety [284] and panic disorders [285]. Kalyn et al [286] assessed therapeutic efficacy, tolerability, and safety of agomelatine in elderly patients observing positive results in depression, anxiety, and anhedonia indicators. On the other hand, anxiolytic action of UCM765 was shown to be mediated by MT 2 receptors [182] and anxiety levels did not alter in MT 2 −/− mice in the EPM [251].…”
Section: Melatoninergic System As a Putative Target For Treating Mmentioning
confidence: 99%